Respuesta :

Answer:

y = 120 ( x - 1/2 ) ( x + 2 )

Step-by-step explanation:

As you can see in every parenthesis there is a coefficient in front of every x term. We do not want them do be there. So we ll eliminate them.

In other words we will factor out from inside each parenthesis the coefficient. So:

[tex]y = - 3(4 - 8x)(5x + 10) \\ y = + 3( - 4 + 8x)(5x + 10) \\ y = 3(8 x - 4)(5x + 10) \\ \\ y = 3(8(x - \frac{1}{2} ))(5(x + 2)) \\ y = 3 \times 8 \times (x - \frac{1}{2} ) \times 5 \times (x + 2) \\ y = (3 \times 8 \times 5)(x - \frac{1}{2} )(x + 2) \\ y = 120(x - \frac{1}{2} )(x + 2)[/tex]